UNDERSTANDING LOVE AND SOCIETY THROUGH EMMA (American Journal of Pedagogical and Educational Research, 2025)
This article provides a detailed analysis of Jane Austen’s novel Emma. The main focus is on themes such as love, marriage, social relationships, and personal development. The study examines the character of Emma Woodhouse, her mistakes, and her journey toward self-awareness. Special attention is given to women’s independence, social class, and moral values in nineteenth-century English society. The relationship between Emma and Mr. Knightley Abstract is analyzed as an example of mature and respectful love. The article is written in simple language and is intended for first-year students to help them better understand the novel.